Physiological and structural aspects of in vitro somatic embryogenesis in Abies alba Mill - Salaj, Terezia; Klubicová, Katarina; Panis, Bartholomeus; Swennen, Rony L.; Salaj Jan (MDPI, 2020)
Initiation of somatic embryogenesis fromimmature zygotic embryos, long-term maintenance of embryogenic tissue in vitro or by cryopreservation, as well as maturation, of somatic embryos of Abies alba Mill. are reported in this study. For the initiation of embryogenic tissues, a DCR medium containing di erent types of cytokinins (1 mg.L􀀀1) were tested. During three consecutive years, 61 cell lines were initiated out of 1308 explants, with initiation frequencies ranging between 0.83 and 13.33%. The type of cytokinin had no profound e ect on the initiation frequency within one given year. Microscopic observations revealed presence of bipolar somatic embryos in all initiated embryogenic tissues. Besides the typical bipolar somatic embryos, huge polyembryonal complexes, as well as “twin” embryos, were observed. Maturation of somatic embryos occurred on a DCR medium supplemented by abscisic acid (10 mg.L􀀀1), polyethylene glycol (PEG-4000, 7.5%) and 3% maltose. The maturation capacity was cell-line dependent. All of the four tested cell lines produced cotyledonary somatic embryos, though at di erent quantities, of 16 to 252 per g of fresh weight. After germination, seedlings developed, but their further growth soon stopped after the formation of a resting bud. Altogether, seven cell lines were cryopreserved, using the slow-freezing technique. After rewarming, all tested cell lines showed regrowth rates between 81.8 and 100%.